Mobile Learning in Mathematics: Benefits, Challenges, Strategies, and Proponents’ and Opponents’ Views - Meylani, Rusen (International Review of Research in Open and Distributed Learning, 2025)
Integrating mobile learning technologies in mathematics education in light of the pandemic, natural disasters, and recent technological developments is a significant shift in practice. This research applied the systematic review approach to assess the impact of mobile learning aids on students’ learning attitudes, motivation, and performance in mathematics. Based on a synthesis of peer-reviewed articles published from 2010 to 2024, this paper focuses on five themes: (a) student and educator experience and engagement, (b) modification in instructional practices, (c) learning and achievements, (d) opportunities, challenges, and strategies, and (e) mobile learning perceptions. The review reveals that mobile learning enhances students’ essential and higher-order thinking skills by establishing interactivity and learning through inquiry. However, other factors, such as the unequal distribution of resources and technology, still pose a challenge. To address these issues, it is suggested that future policies should focus on improving infrastructure, digital competency, and professional learning for instructors. Further, it is essential for institutions to engage faculty members in collaborative platforms to enhance their practice and have secure measures for data protection. This systematic review emphasizes the need for the researcher to conduct these evaluations over time to gauge the long-term impact of mobile learning and to look at the effects of this form of learning on different groups of students. It also concludes that future studies need to pay attention to ethical concerns and ways to provide equal opportunities in integrating technology into mathematics education for all students.